Public say food regulatory policies to improve health in Western Australia are important: population survey results. (1st October 2013) - Pollard, Christina M.; Daly, Alison; Moore, Michael; Binns, Colin W.
Abstract Objective: To investigate the level of support among Western Australian adults for food control policies to improve diet, reduce obesity and protect the environment. Methods: Attitudes towards government food control policies on food labelling, food advertising, and the supply of environmentally friendly food data were pooled from two Nutrition Monitoring Survey Series telephone surveys of 2, 147 adults aged 18–64 years collected in 2009 and 2012. Descriptive and logistic regression analyses were conducted using survey module of STATA 12. Results: The majority of adults believe it is important that government regulates food policy options under consideration: nutrition information on food labels (97% versus 2% who think it is not important); health rating on food labels (95% versus 3%); food advertising (83% versus 11%); and the supply of environmentally friendly food (86% versus 9%). Conclusions: Community perception is that government control or regulation of food labelling, food advertising and the supply of environmentally friendly food is important. Implications: Curbing excess weight gain and related disease burden is a public health priority. Australian governments are considering food regulatory interventions to assist the public to improve their dietary intake. These findings should provide reassurance to government officials considering these regulatory measures.